2002
DOI: 10.1007/bf02347695
|View full text |Cite
|
Sign up to set email alerts
|

Modelling induction of a rotor in cardiac muscle by perpendicular electric shocks

Abstract: A strong, properly timed shock applied perpendicularly to a propagating wavefront causes a rotor in the canine myocardium. Experimental data indicate that the induction of this rotor relies on the shock exciting tissue away from the electrodes. The computational study reproduced such direct excitation in a two-dimensional model of a 2.7 x 3 cm sheet of cardiac muscle. The model used experimentally measured extracellular potentials to represent 100 and 150 V shocks delivered through extracellular electrodes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Since the first attempt by Moe et al [1963], many theoretical studies have used a modeling approach to understand and characterize different types of reentry in excitable media [Van Capelle & Durrer, 1980;Winfree, 1989;Leon et al, 1994;Starmer et al, 1995;Efimov et al, 1995;Rudy, 1995;Xu & Guevara, 1998;Biktashev et al, 1999;Ferrero, Jr. et al, 2000;Xie et al, 2001;Small et al, 2001;Skouibine et al, 2002;Bernus et al, 2002;among others]. However, the majority of these theoretical works have modeled the normal (non-ischemic) myocardium, with very few studies having dealt with the acutely ischemic myocardium, in which reentrant tachycardias and fibrillation are most likely to occur in vivo.…”
Section: Introductionmentioning
confidence: 97%
“…Since the first attempt by Moe et al [1963], many theoretical studies have used a modeling approach to understand and characterize different types of reentry in excitable media [Van Capelle & Durrer, 1980;Winfree, 1989;Leon et al, 1994;Starmer et al, 1995;Efimov et al, 1995;Rudy, 1995;Xu & Guevara, 1998;Biktashev et al, 1999;Ferrero, Jr. et al, 2000;Xie et al, 2001;Small et al, 2001;Skouibine et al, 2002;Bernus et al, 2002;among others]. However, the majority of these theoretical works have modeled the normal (non-ischemic) myocardium, with very few studies having dealt with the acutely ischemic myocardium, in which reentrant tachycardias and fibrillation are most likely to occur in vivo.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have found that the small spatial scale heterogeneities in cardiac tissue may influence field stimulation and defibrillation 10–12,17–18 . Fishler represented the syncytial heterogeneities of cardiac tissue by varying the conductivities and the surface‐to‐volume ratio in the bidomain model 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Monodomain simulations were performed using the openCARP simulation environment ( Plank et al, 2021 ) with baseline conductivity values of 0.03, 0.02 and 0.02 S/m for longitudinal ( σ L ), transverse ( σ T ) and transmural ( σ S ) directions. Using time steps of 0.05 ms throughout, a planar wave was generated by stimulating one transmural surface of the slab with shortening coupling intervals at 0, 325, 525 and 715 ms. A rotating wave was then generated by applying a cross field stimulus during the recovery phase of the central portion of the model at 860 ms ( Skouibine et al, 2002 ). To emulate experiments and signal morphology specific to optical mapping, the cardiac arrhythmia research package ( Vigmond et al, 2003 ) was used to generate epi-fluorescent optical signals from electrical simulations, as described previously ( Bishop et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%